Multi-objective optimization of the organic Rankine cycle cascade refrigeration cycle driven by sugar mills waste heat - Wang, Zongrun; Guan, Wei; Zhang, Song; Sang, Hailang; Que, Wenshuai; Liang, Lu (Frontiers in Energy Research, 2024)
The research on the recovery of low-grade thermal energy carried away by boiler flue gas is significant for sugar mills. This paper designs a waste heat recovery system based on sugar plant flue gas, integrating absorption refrigeration cycle and the organic Rankine cycle. The aim is to realize the multi-form conversion of energy. The performance of the system is evaluated in terms of energy, exergy, and economic metrics. The influence of nine working fluids on the system is investigated. The results show that Butane is the most suitable working fluid for ORC. The exergy efficiency of the system is 32.125%, with an increased space cooling capacity of 15820.56 MW per year for the sugar mill. Multi-objective optimization is performed with the method of the NSGA-II genetic algorithm. The entire system shows a high total exergy efficiency of 31.57% under the optimized condition, and the LCOE is as low as 0.0406/kWh. The optimized system can obtain an estimated annual electricity sales revenue of 136,300, and the sugar mill can save 308,600 in cooling costs. The exergy destruction analysis of the system reveals that the generator accounts for the highest proportion of exergy destruction (50.8%). In addition, the payback period can be shortened to 5.79 years.